Hierarchical metal nanomesh/microgrid structures for high performance transparent electrodes1. Issue 87 (20th September 2015) - Gao, Tongchuan; Huang, Po-Shun; Lee, Jung-Kun; Leu, Paul W.
<x xml:space="preserve">Abstract</x> We report a comprehensive study on the optical and electronic properties of hierarchical metal nanomesh (NM)/microgrid (MG) structures to evaluate their performance as transparent conductors (TCs).